Clinical manifestations and long-term outcomes of IgG4-related kidney and retroperitoneal involvement in a United Kingdom IgG4-related disease cohort - Evans, R; Cargill, T; Goodchild, G; Oliveira, B; Rodriguez-Justo, M; Pepper, R; Connolly, J; Salama, A; Webster, G; Barnes, E; Culver, E (Elsevier, 2018)
Introduction IgG4-related disease (IgG4-RD) is a relapsing multisystem fibro-inflammatory disease, which may involve the kidney (IgG4-related kidney disease [IgG4-RKD]) and retroperitoneum (IgG4-related retroperitoneal fibrosis [IgG4-RPF]). The aim of this study was to describe IgG4-RKD and IgG4-RPF in the United Kingdom. Methods We conducted a retrospective observational study of patients with IgG4-RKD and IgG4-RPF in a multicenter IgG4-RD cohort. Data were collected through review of medical records. We describe clinical parameters at baseline, histological and radiological findings, treatment, and patient outcomes. Results Of 154 patients with IgG4-RD, 14 (9.1%) had IgG4-RKD, 10 (6.5%) had IgG4-RPF, and 4 (2.6%) had both. Patients were aged 58.2 ± 14.2 years, and 26 (92.9%) were male. Creatinine at presentation was worse in those with intrinsic renal disease (229 μmol/l vs. 110 μmol/l; P = 0.0076). Serum IgG4 was elevated in the majority of patients (87.5%), and hypocomplementemia was present in half of those with IgG4-RKD. Fifteen patients underwent renal biopsy; tubulointerstitial nephritis with abundant IgG4+ plasma cells was the most common finding (n = 14; 93.3%), and 4 (26.7%) patients had membranous nephropathy. Most patients (89.3%) were treated with corticosteroids, and 4 (16.0%) with additional azathioprine as initial management. Thirteen patients (46.4%) relapsed over 60 ± 48 months of follow-up, at median 18 (12–36) months after renal/RPF diagnosis; 61.5% of relapses were in the kidney. Renal function deteriorated in 5 patients (20.8%), including 2 (8.3%) who reached end-stage renal disease (ESRD). Conclusion IgG4-RKD and IgG4-RPF represent major organ manifestations of IgG4-RD, and should be identified early with prompt treatment to prevent progression to ESRD.